TEACHING AND INNOVATION AT THE UNIVERSITY: OF "LIVING" CONCEPTIONS AND PRACTICES - Erika Yamila Sánchez; Patricia Belén Demuth (Revista del Instituto de Investigaciones en Educación, 2019)
The following article focuses on the results of research on university teaching, particularly in the analysis of a case contextualized in a subject of the Architecture career recognized as an innovative pedagogical practice of the Universidad Nacional del Nordeste. Our main objective is to understand the foundations of innovative pedagogical practices built by teachers through their professional practice. Methodologically, it works from an interpretative paradigm and a qualitative approach, with case studies. The data collection instruments were micro-interviews before and after the classes, in-depth interviews, observations of non-participating classes and analysis of curricular documents. As conclusions we point out the reconstruction of a case of university teaching whose pedagogical and didactic proposal was sustained in a community of scarce economic resources, which acted as a scenario of the didactic proposal from a critical perspective, relate a "living laboratory", the disciplinary dimension, the active student role and the evaluation of authentic learning.